2013
DOI: 10.1080/10967494.2013.796257
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation, Task, and Non-task Behavior: A Performance Appraisal Experiment with Korean MPA and MBA Students

Abstract: Appraisals of public employees are important for a host of reasons, and particularly so with the increasing emphasis on pay-for-performance systems and performance-based management in the public sector. However, managerial appraisals of employees can be somewhat subjective and our understanding of the appraisal process in the public sector is largely U.S.-centric. In this study, we explore whether characteristics of managers, like a rater's public service motivation (PSM), affect appraisal outcomes for their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 98 publications
5
55
0
2
Order By: Relevance
“…A small number of promising experimental studies have already been published (Bellé, 2013(Bellé, , 2014Christensen et al, 2013;Moynihan, 2013) and additional experimental studies are in development or under peer review.…”
Section: Foundations For the Third Wavementioning
confidence: 98%
“…A small number of promising experimental studies have already been published (Bellé, 2013(Bellé, , 2014Christensen et al, 2013;Moynihan, 2013) and additional experimental studies are in development or under peer review.…”
Section: Foundations For the Third Wavementioning
confidence: 98%
“…Consistent with Christensen et al (2013), we consider two types of OCBs: discretionary behaviours of benefit to the organisation (OCBO) and employees (OCBI) (see also Williams and Anderson 1991). OCBOs capture aspects of identification, commitment and loyalty to the organisation (such as defending the organisation when others criticize it, and showing pride when representing the organisation in public).…”
Section: Transformational Leadership and Ocbsmentioning
confidence: 99%
“…Although OCBs are one of the most widely studied topics in the fields of organisational behaviour and general management, relatively few studies have considered these behaviours in public administration (Kim 2006;Christensen et al 2013;Taylor 2013). …”
Section: Transformational Leadership and Ocbsmentioning
confidence: 99%
“…We therefore also assess the public service motivation of supervisors and investigate whether this plays a role. As Christensen et al (2013) observed, supervisors with high PSM may be more compassionate and therefore provide higher ratings. However, it could equally be that supervisors with high PSM may, like employees, put in more effort and work harder and thus are in charge of work units that perform above average.…”
Section: 3mentioning
confidence: 66%
“…Wright and Grant (2010) argue that supervisors in public organizations may 'have a predilection toward employees with high PSM' (p.695) because such employees express compassion and volunteer for extra work tasks. Christensen et al (2013) showed empirically that appraisal scores given by supervisors were influenced by the supervisor's own PSM. Our study addresses the potential bias in supervisor ratings in two ways.…”
Section: 3mentioning
confidence: 99%